Clinical Assessment and Etiological Evaluation of Optic Nerve Atrophy - Shrestha, Pranav; Sitaula, Sanjeeta; Sharma, Ananda Kumar; Joshi, Purushottam (Nepalese Journal of Ophthalmology, 2021)
Introduction: Optic atrophy results from the disease process that cause irreversible damage to the ganglion cells and the anterior visual pathway, but may also result from posterior visual pathway involvement. The etiology causing this condition is vast and regardless of underlying cause it carries bad visual prognosis and at times may be life threatening. The study aims to assess patients with optic nerve atrophy presenting to B.P. Koirala lions centre for ophthalmic studies and identify the underlying etiology. Materials and methods: This is a descriptive study conducted at B.P. Koirala Lions Centre for Ophthalmic studies. All cases of optic atrophy who presented to our outpatient department from March 2016 to March 2017 were included in the study. In addition to detailed evaluation, assessment of visual acuity, color vision, contrast sensitivity and visual field were done if feasible. Other relevant investigations were conducted to establish the underlying etiological cause. Results: A total of 62 patients were included in the study, with 35 patients having bilateral disease and 27 having unilateral disease accounting for 97 eyes with optic atrophy. The mean age of the affected was 40.63±17.36 years with male to female ratio of 1.2:1. The most common etiology for optic atrophy was traumatic neuropathy (n=16, 25.8%). Majority of eyes had pale disc (n=70, 72.2%) and the rest had temporal pallor (n=27, 27.8%). Conclusion: Traumatic optic neuropathy was the most common etiological cause of optic nerve atrophy.